2013
DOI: 10.1155/2013/135142
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Two Lactobacillus plantarum Strains on Rat Lipid Metabolism Receiving a High Fat Diet

Abstract: The aim of our study was to evaluate the effects of the different probiotic strains, Lactobacillus plantarum LS/07 and Lactobacillus plantarum Biocenol LP96, on lipid metabolism and body weight in rats fed a high fat diet. Compared with the high fat diet group, the results showed that Lactobacillus plantarum LS/07 reduced serum cholesterol and LDL cholesterol, but Lactobacillus plantarum Biocenol LP96 decreased triglycerides and VLDL, while there was no change in the serum HDL level and liver lipids. Both pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 41 publications
5
36
2
3
Order By: Relevance
“…Although values for triglycerides [27,32] and glucose [25] decreased in some studies on probiotic microorganisms, we did not experience this in our study.…”
Section: R E S U L T S a N D Discussioncontrasting
confidence: 69%
“…Although values for triglycerides [27,32] and glucose [25] decreased in some studies on probiotic microorganisms, we did not experience this in our study.…”
Section: R E S U L T S a N D Discussioncontrasting
confidence: 69%
“…Lactobacillus rhamnosus administration alone caused a significant reduction in the β-glucuronidase activity in the first week, but the enzyme activity went back to normal in the fourth week. While a previous study also reported that probiotics, L. rhamnosus GG and L. acidophilus, could inhibit the β-glucuronidase activity in the caecum of both lean and obese animals (Salaj et al, 2013), we observed only temporary changes. Furthermore, we introduced a consistent antibiotics intervention to mimic the antibiotics treatment in daily soymilk or fermented soymilk consumption.…”
Section: Discussioncontrasting
confidence: 91%
“…However, some studies observed that rat body weight gain was similar in both groups (control and kefir); No significant differences were found (Elena et al, 2007;Sahin and Yardimci, 2009;Ataşoğlu et al, 2010;Kızak and Çelik, 2012;Aliakbarpour et al, 2013;Salaj et al, 2013;Piccolo et al, 2015).…”
Section: Discussionmentioning
confidence: 97%